Exploring Grade 10 learners’ perceptions of the importance of Economics subject in Turffontein Secondary schools - Olagunju, Olayinka Samual (My University, 2019)
The purpose of this study was to explore Grade 10 learners’ perception of the importance of economics subject in selected secondary schools in Turffontein, Gauteng province, South Africa. Furthermore, the study sought to identify factors that shape learners’ perception of the importance economics subject. This study used phenomenological qualitative approach to interrogate learners’ perception of economics subject, and data was collected through semi-structured one-to-one individual interviews and focused group interviews. Four learners from each schools participated in the semi-structured one-to-one individual interviews, and eight learners from both schools participated in the focused group interviews. Critical discourse analysis was used as theoretical framework and Fairclough’s analytical framework of critical discourse analysis was used as a lens to makes sense of the meaning provided by learners about their perceptions of the importance of economics subject. The results from data analysis reveal the following. First, learners perceived that economics as a subject has value. Regards for economics seem to come from learners’ belief that studying it help them understand real life issues and offers a path to their future career. Second, they thought of economics as a social science and synonymous with history. Third, Factors such as the prospect of getting a job and the influence of peers were identified as factors that shape these perceptions. This suggested that learners’ choice of studying economics is influenced by extrinsic factors. These findings have considerable implications for further research, policy and practice, as well as the nature of the subject itself.
A research dissertation presented to the Faculty of Humanities (School Of Education), July 2019